Workshop on Islamic financial literacy at MTs Muhammadiyah 1 Malang - Fadilla Muhammad Mahdi; Arif Luqman Hakim (Universitas Muhammadiyah Magelang, 2024)
The purpose of this community service activity is to improve Islamic financial literacy among students of Madrasah Tsanawiyah (MTs) Muhammadiyah 1 Malang City. This community service was conducted because Islamic financial literacy in Indonesia, especially among students, is still relatively low, while understanding the principles of Islamic finance is very important in order to support the rapid development of the Islamic finance industry. The method used is a workshop, where participants are given material on Islamic finance interactively. The results of this program indicate a significant increase in Islamic financial literacy among participants. In addition, as a follow-up, a joint Islamic savings account was opened for 8th-grade students, which is expected to encourage direct practice of the Islamic financial principles that have been learned.